Effectiveness of 8‐ or 12‐weeks of ledipasvir and sofosbuvir in real‐world treatment‐naïve, genotype 1 hepatitis C infected patients. Issue 5 (10th July 2017) - Curry, M. P.; Tapper, E. B.; Bacon, B.; Dieterich, D.; Flamm, S. L.; Guest, L.; Kowdley, K. V.; Lee, Y.; Milligan, S.; Tsai, N.; Younossi, Z.; Afdhal, N. H.
Summary: Background: Treatment of genotype 1 hepatitis C virus (HCV) infection with combination direct acting anti‐virals is associated with very high rates of sustained virological response (SVR). Daily combination of ledipasvir and sofosbuvir for 12 weeks is approved for the treatment of genotype 1 HCV patients, though noncirrhotic patients who are naïve to treatment with a baseline HCV RNA <6 million IU/mL can be treated for 8 weeks. This guidance stemmed from a post hoc analysis of the ION 3 clinical trial, which demonstrated similar SVR for patients treated with ledipasvir and sofosbuvir with or without ribavirin for 8 or 12 weeks. Aim: To compare the SVR for 8 weeks vs 12 weeks of ledipasvir and sofosbuvir in HCV infected patients in a real‐world setting. Methods: We performed an observational real‐world cohort study of treatment success following 8 or 12 weeks of ledipasvir and sofosbuvir for treatment‐naïve genotype 1 HCV patients. Results: A total of 826 patients were treated for either 8 (n=252) or 12 weeks (n=574) with ledipasvir and sofosbuvir and achieved SVR rate of 95.3% and there was no statistical difference in SVR rates in the two groups irrespective of any clinical or virological variables. Conclusions: In treatment‐naïve HCV genotype 1 patients, SVR was 95% in those treated for either 8 weeks or 12 weeks with ledipasvir and sofosbuvir. 8 week ledipasvir and sofosbuvir can reduce costs without compromising outcomes for those patients who qualify for such regimen.